PERAN PEMERINTAH DESA DALAM PENDATAAN KEPENDUDUKAN DI DESA BANDUR PICAK KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR TAHUN 2014-2016 - Irwandi, Ahmad; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Population Administration is a very important role in development, where the system of Population Administration can be known about the population data and information in accordance with the state of the population and about the condition of the area of residence of the population. Provisions governing the Village Administration are regulated in the Minister of Home Affairs Regulation No. 47 of 2016 on Village Administration of Village Heads authorized to organize Village Administration. The village head implements village administration assisted by village officials. Village Administration is implemented in the framework of: Governance, Development Implementation, Community Development, and Community Empowerment.The research method used in this research is qualitative research, with the focus of research: (1) The Role of Village Government in Population Data Collection In Bandur Picak Village Koto Kampar Hulu Sub-District (2) Factors Influencing Implementation of Role of Bandur Picak Village Government in Population Data Collection in Bandur Picak Village.The result of the research is that the implementation of the role of village government as the administrative organizer of the village has not been maximally can be seen from the implementation of the role of village government, in data collection and handling of moving documents, there are still many immigrants who have no identity including the letter moved from their place of origin. While the sanctions provided by the village government are not in accordance with the rules contained in the village regulations. So the rules made by the village government from 2014-2016 do not work.Keywords: Role of Village Government, Order of Population Adm